2000
DOI: 10.1093/her/15.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Process measures in an antenatal smoking cessation trial: another part of the picture

Abstract: Data on provider and patient compliance can be crucial in understanding the degree of a health education program's effectiveness, as well as in identifying areas where the program requires modification. However, such data are rarely systematically reported in randomized trials. This report assesses the degree to which doctors and midwives complied with intervention protocols in a hospital antenatal smoking cessation trial, and also examines the program's acceptability to patients. Provider compliance was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Process evaluation is a useful technique for understanding how well programmes are being implemented, and can be useful for identifying factors that contribute to or detract from smooth implementation[23,24]. This study showed that the implementation of the birth plans intervention was successful, but that providers need more training and support to implement other aspects of the focused ANC model.…”
Section: Discussionmentioning
confidence: 99%
“…Process evaluation is a useful technique for understanding how well programmes are being implemented, and can be useful for identifying factors that contribute to or detract from smooth implementation[23,24]. This study showed that the implementation of the birth plans intervention was successful, but that providers need more training and support to implement other aspects of the focused ANC model.…”
Section: Discussionmentioning
confidence: 99%
“…Our use of direct observation data collection method is also a study limitation because of the potential for participants’ reactivity owing to the field investigator’s presence in the counseling room (Bentley et al, 1994; Curtis et al, 1993; Patton, 1990; Redman, Dickinson, Cockburn, Hennrikus, & Sanson-Fisher, 1989; Walsh et al, 2000). To address reactivity, the research design included observing many (at least 20) counseling sessions for each nurse to give the nurse and field investigator time to get used to each other’s presence in the room and for the nurse to return to her habitual counseling behaviors (Patton, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Use of direct observation methods is also a strength of our study because it is an effective approach to assess program implementation (Patton, 1990; Walsh et al, 2000). A few researchers reported using this method to observe health provider’s infant-feeding counseling behaviors (Chopra et al, 2005; Chopra & Rollins, 2008; Horizon Program, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, this information can inform researchers, policy makers and practitioners about how the intervention might be implemented in future. We could only identify a few smoking cessation and pregnancy trials which have reported process data and there was very limited information about the experience of those delivering the intervention [4–6]. …”
Section: Introductionmentioning
confidence: 99%